FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA BARU TAHUN AJARAN 2022/2023 PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Simanihuruk, Peran; Manihuruk, Christinus (UNIKA Santo Thomas, 2023)
The aim of the research is to analyze the factors that influence the decisions of new students for the 2022/2023 academic year of the lecture management study program at the Faculty of Economics, Catholic University of Santo Thomas Medan. Total sample of 189 respondents, data collection with questionnaires and documentation, method of analysis with factor analysis. The results showed that of the 36 factors that most dominantly influenced the decision of new students T.A 2022/2023 to study at the Catholic University of Economics, Santo Thomas Medan, it turned out that the most dominant were: Factor 1: Compatibility of subjects with a variety of courses, accreditation status, having student dormitory Image, quality of education and reputation. Factor 2 : Opportunity to get a scholarship , Public transportation, Has sports facilities and curriculum. Factor 3: Guaranteed future income, graduate quality and interest. Factor 4: Ease of getting a job, strategic campus location and complete facilities. Factor 5: More affordable tuition fees and expected job suitability. Factor 6: Family encouragement and tuition fees can be paid in stages. Factor 7 : Improving the social status of the family and Improving the economic situation of the family. Factor 8: Lecture time is more flexible and educational staff. Factor 9: Number of teaching staff, parental encouragement and recommendations from schools. Factor 10: Environmental security and the expected work in accordance with the choice of major. Factor 11: Quality of teaching staff and encouragement of friends. Factor 12: Greater job opportunities are accepted and alumni success. Factor 13: Having a commitment to learn, Creating a better future and Alumni recommendations. Researchers who only examined 36 factors, it is hoped that researchers will add further research indicators that are considered to influence prospective students in choosing a college study program. This research can be used as a reference for consideration in improving further research as well as for higher education management. For further research, it is hoped that the researcher will be able to increase the number of respondents who are sampled for potential student candidates.